2015
DOI: 10.1039/c5cp00817d
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanism of fluoride adsorption from aqueous solutions onto Fe-impregnated chitosan

Abstract: a granular Fe-impregnated chitosan (Fe-CTS) adsorbent was synthesized via chelation of Fe ions to -OH and -NH2 groups of CTS. The Fe-CTS granular adsorbent exhibited high performance for the adsorption of fluoride. The mechanism of fluoride adsorption on Fe-CTS was elucidated using EXAFS and FTIR analyses. Fluoride adsorption on Fe-CTS occurred via ion exchange between chloride and fluoride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…It was observed that fluoride interacts with the OH and NH groups on surface aluminum-impregnated coconut fiber surface [140]. However, the adsorption of fluoride on Fe-impregnated chitosan was reported to occur due to ion exchange between fluoride and chloride [141]. Other studies using FTIR have revealed the formation of inner-spherically bonded complexes on −Fe2O3 nanoparticles with fluoride [142].…”
Section: Fluoride (F − ) Adsorption Isotherm and Adsorption Capacitymentioning
confidence: 94%
See 1 more Smart Citation
“…It was observed that fluoride interacts with the OH and NH groups on surface aluminum-impregnated coconut fiber surface [140]. However, the adsorption of fluoride on Fe-impregnated chitosan was reported to occur due to ion exchange between fluoride and chloride [141]. Other studies using FTIR have revealed the formation of inner-spherically bonded complexes on −Fe2O3 nanoparticles with fluoride [142].…”
Section: Fluoride (F − ) Adsorption Isotherm and Adsorption Capacitymentioning
confidence: 94%
“…The effects of these anions on fluoride adsorption have also been reported to be different depending on experiment conditions which include pH, the anions concentrations, and the characteristics of the adsorbent. Recently, Zhang et al [141] reported that the increasing concentrations of sulfate and carbonate to 200 mg/L cause a decrease in the fluoride adsorption by 43.24% and 18.77%, respectively, while 100 mg Cl − /L increases the fluoride adsorption capacity of 0.58 mg/g by 2.53 mg/g with 5 mg of HCO 3 . For the former, the decrease was because of the electrostatic interactions of the anions and the adsorbent, and for the latter, the reaction of bicarbonate with ammonium acetate leads to the decrease of the ammonium acetate concentration.…”
Section: Effects Of Anion Cation and Organicmentioning
confidence: 99%
“…48,49 The effects of coexisting oxygen anions that are typically present in groundwater on uoride removal are shown in Fig. 6, and the ion concentrations and pH values of solution before and aer uoride adsorption for co-existing oxygen anions are shown in ) had hardly any adverse effects on uoride removal in the range of 0-100 mg L À1 (Fig.…”
Section: Effect Of Co-existing Oxygen Anionsmentioning
confidence: 99%
“…is an ion exchange process between fluoride and chloride or sulfate 642 due to their connatural chemical properties, but fluoride has 643 greater selectivity than that of co-existing anions, which allows 644 adsorbed sites with chloride or sulfate to be replaced by fluoride 645 [56]. More detailed research on fluoride removal using fixed-bed 646 column experiments including study of the competition and 647 adsorption mechanisms between fluoride and other co-existing 648 anions, the effects of various operational parameters (e.g., flow 649 rate, fluoride concentration, column diameter and height, etc.…”
mentioning
confidence: 99%